Laser-Assisted Scattering with Screened Diatomic Potential - Asmit Sapkota; Saddam Husain Dhobi; Subash Khatiwada (Program Studi Fisika Universitas Negeri Jakarta, 2024)
This study explores the differential cross section (DCS) for laser-assisted scattering of diatomic molecules, considering various polarization conditions (linear, circular, elliptical) and potential parameters. The primary objective is to understand how polarization, screening effects, and potential parameters influence the scattering behavior. Utilizing a model that incorporates the Morse potential with screening effects, the analysis treats the laser field classically as a time-dependent, spatially homogeneous electric field, while the electron dynamics are described quantum mechanically using the Schrödinger equation. The Volkov wavefunction is derived, and the first-Born S-matrix element is computed to evaluate the scattering process. The results show that the DCS decreases with increasing screening parameters, with linear polarization yielding higher values than circular or elliptical polarization. Specifically, at an initial momentum of 8 MeV and a final momentum of 9 MeV, the DCS for elliptical polarization is notably higher. The DCS also varies with potential strength and well width, showing a peak at 0.14 Å for potential well width. The findings suggest that linear polarization is most effective for scattering studies under varying potential strengths. It is recommended to focus on linear polarization for enhanced scattering efficiency and to carefully adjust screening parameters and potential well widths for optimal results.